Mallotus furetianus extract protects against ethanol‐induced liver injury via the activation of the cAMP‐PKA pathway. Issue 7 (10th June 2020) - Yoshikawa, Eri; Matsui‐Yuasa, Isao; Huang, Xuedan; Kobayashi, Yoshinori; Kojima‐Yuasa, Akiko
Abstract: The protective effects of Mallotus furetianus extract (MF) on liver fibrosis induced with ethanol were examined using in vivo and in vitro model. MF treatment suppressed plasma alanine aminotransferase and aspartate aminotransferase activities in ethanol plus carbon tetrachloride (CCl4 )‐induced cirrhosis rat model. MF also suppressed the increase in type l collagen and α‐smooth muscle actin expression in the livers of ethanol plus CCl4‐induced rat by the maintenance of intracellular glutathione levels. Furthermore, we evaluated the effect of MF on the alcohol‐induced activation of hepatic stellate cells (HSCs), which are responsible for the increased production and deposition of the extracellular matrix in liver injury. Here, we observed the enhancement of the intracellular reactive oxygen species (ROS) levels and the increase in type I collagen and a‐SMA expression in HSCs activated with ethanol. However, the enhanced ROS levels were suppressed with the treatments of MF or diphenyleneiodonium (DPI). Furthermore, the treatment of MF or DPI suppressed the increase in type I collagen and a‐SMA expression activated with ethanol. We also observed that the treatment of MF or LY194002 suppressed the increase in type I collagen expression in HSCs activated with ethanol, suggesting that ethanol induced type I collagen expression via the PI3K‐Akt signaling pathway. On the other hand, the suppression of the synthesis of type I collagen in ethanol and MF‐treated HSCs was inhibited by H‐89. From these results, MF may suppress the increase in the activity of NADPH oxidase in HSCs activated with ethanol through the cAMP‐PKA pathway. Abstract : Mallotus furetianus extract (MF) suppressed the development of alcoholic liver fibrosis. MF suppressed the alcohol‐induced activation of hepatic stellate cells. MF suppressed the increase in the activity of NADPH oxidase in HSCs activated with ethanol through the cAMP‐PKA pathway.